When Ritual Becomes Protest: Crossing the Bridge of Russian Mourning - Sokolova, Anna (Javnost-The Public, 2020)
Grassroots memorials have become well known for scholars since the 1980s. The researchers mostly place these practices in between public grievances and grassroots political protest. I propose a not less productive way to analyse these kinds of memorials, considering them as a channel for self-representation in the public sphere that is used by margin social and political groups. In societies where access to the public sphere is limited, a non-conventional mechanism that lets margin groups represent themselves via non-political practices, such as a funeral rite, may appear. The public nature of the funeral rite allows political groups to use it as an occasion to mobilise supporters. The commemorative background of these gatherings prevents them from being considered as a political manifestation, nor do they have any organiser who could be legally penalised. Thus, death-related rituals, including grassroots memorialisation, appear to be an effective channel for margin political groups to represent themselves and even to state and promote their political ideas. In this paper, I will analyse this phenomenon using current Russian observational data and show how these practices become an important channel for political opposition in Russia to communicate with the electorate, opponents and authority.